Developing 'good buggers': global implications of the influence of culture on New Zealand club rugby coaches' beliefs and practice. Issue 8 (3rd August 2018) - Hassanin, Remy; Light, Richard L.; Macfarlane, Angus
Abstract: Despite recognition of how experience shapes sport coaches' beliefs and practice empirical investigation into how this occurs is limited. This article redresses this gap in the literature by presenting the findings of a study that inquired into the influence of culture on three New Zealand rugby coaches' beliefs and practice to identify the powerful influence of interaction between a 'local' traditional culture of club rugby in New Zealand shaped by the resilient 'amateur ideal', intensified by the perceived threat of professional rugby and the global culture of the sport industry to club rugby.